PENGABDIAN KEPADA MASYARAKAT SEMINAR NASIONAL ONLINE “KOMPETENSI, PELUANG, DAN TANTANGAN PEREKAM MEDIS & INFORMASI KESEHATAN DI ERA INDUSTRI 4.0 - Meliana; Garis Gemilang; Indah Kristina; Ima Rusdiana (APIKES Bhumi Husada Jakarta, 2022)
Community Service is one of the Tri Dharma of Higher Education, namely education, research, and community service. One of the realizations of community service carried out by APIKES BHJ is in the form of a national seminar with the theme